UJI EFEKTIVITAS KOMPOS KOTORAN SAPI DAN SEKAM PADI MENGGUNAKAN MIKROORGANISME LOKAL BATANG PISANG TERHADAP POPULASI BAKTERI PELARUT FOSFAT DAN PRODUKSI PAKCOY (Brassica rapa var. chinensis L.) - Megalia Himawarni; Yulia Nuraini (Departemen Tanah, Fakultas Pertanian, Universitas Brawijaya, 2022)
Management of agricultural land in Jabung District using inorganic fertilizers with high doses resulted in a decrease in soil quality, such as a low population of phosphate solubilizing bacteria that can release phosphate from Al-P and Fe-P bonds. Inceptisols in Jabung Subdistrict with low fertility still has the potential to cultivate pakcoy with the innovative application of cow manure and rice husk compost with banana stem MOL bioactivator as a source of bacterial culture and organic matter decomposers. This study was aimed to determine the effectiveness of the application of cow dung and rice husk compost on the population of phosphate solubilizing bacteria, the diversity of bacteria in dissolving phosphate based on the clear zone index, and the yield of pakcoy. This study used a randomized block design with six treatments and four replications. The results showed that cow dung and rice husk compost significantly increased the population of phosphate solubilizing bacteria by 27.7 × 106 CFU g-1, diversity of phosphate solubilizing bacteria based on the clear zone index as many as 23 isolates with the highest clear zone index 5,40 isolate code P52. The results also showed that the application of cow dung and rice husk compost significantly increased the wet weight by 15,520 kg ha-1 and the dry weight of pakcoy by 661.6 kg ha-1.